Acupuncture for children with autism spectrum disorder: A systematic review and meta-analysis. Issue 8 (22nd February 2023) - Lun, Tingting; Lin, Shaoping; Chen, Yuecai; Zhao, Yunxuan; Wang, Dexin; Li, Li; Yu, Jin
Abstract : Background: The aim of this study was to assess the efficiency and safety of acupuncture in core symptomatic improvement of children with autism spectrum disorder (ASD). Methods: We searched the following databases: Cochrane Library, PubMed, Embase, Medline, China National Knowledge Infrastructure (CNKI), Wanfang, Chinese Science and Technology Periodical (VIP) and Chinese Biological Medicine (CBM), from 1 January 2012 to 25 September 2022. The Autism Behavior Checklist (ABC), Childhood Autism Rating Scale (CARS), and Autism Treatment Evaluation Checklist (ATEC) were adopted as outcome indicators. Three reviewers independently assessed the risk of bias (ROB) and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE)assessment. Utilizing Review Manager (RevMan) 5.3 and Stata 12.0, data were analyzed. Results: A total of 38 trials were included, and 2862 participants participated in qualitative synthesis and meta-analysis. Only 1 trial was assessed as having a low ROB, and 37 trials were assessed as having an overall high ROB. The quality of evidence for most indicators were considered very low by the GRADE criteria. The results showed that acupuncture groups might have a higher clinical effective rate than nonacupuncture groups (relative risk [RR] = 1.33, 95% confidence interval [CI] = 1.25–1.41; heterogeneity: x 2 =18.15, P = .64, I 2 = 0%). Regarding changes in ABC scores, the acupuncture groups might exhibit greater decrease than nonacupuncture groups (MMD = −6.06, 95%CI = −7.25 to −4.87, P < .00001; heterogeneity: x 2 =73.37, P = .03, I 2 = 77%). In terms of changes in CARS score, acupuncture group may benefit more than nonacupuncture group (MMD = −3.93, 95%CI = 4.90 to −2.95, P < .00001; heterogeneity: x 2 =234.47, P < .00001, I 2 = 90%). Additionally, in terms of ATEC score, acupuncture groups showed more benefit than nonacupuncture groups (MMD = −10.24, 95%CI = −13.09 to −7.38, P < .00001; heterogeneity: x 2 =45.74, P = .04, I 2 = 85%). Both subgroup analysis and sensitivity analysis are existing heterogeneity. Only 1 RCT study involved adverse events with mild symptoms that did not interfere with treatment and evaluation. Conclusion: Children with ASD may benefit from acupuncture because of its effectiveness and safety. Nevertheless, given the low quality of the evidence for the assessed outcomes and the high ROB of analyzed trials, the results should be regarded with caution.